1997
DOI: 10.3109/00365599709030642
|View full text |Cite
|
Sign up to set email alerts
|

Penile Tourniquet: An Invaluable Technique

Abstract: In 72 cases of minor penile surgeries, including circumcision (42), meatotomy (18), meatoplasty (8) and chordee correction (4), a ring cut from a surgical glove finger was used as a tourniquet at the base of the penis after infiltrating the skin and the glans with plain 1% xylocaine. The usual surgical procedures were performed and the tourniquet was released after securing the probable bleeding points. The postoperative results were excellent, with oedema of the penis being the only complication. There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although diff erent types of tourniquets have been used in hypospadias repair over the years, the true incidence of complications due to PT is not known. Pathak et al reported penile edema in 4.7 % of cases [14] . Davis and Harrold reported graft failure after tourniquet usage in two-staged hypospadias repair [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Although diff erent types of tourniquets have been used in hypospadias repair over the years, the true incidence of complications due to PT is not known. Pathak et al reported penile edema in 4.7 % of cases [14] . Davis and Harrold reported graft failure after tourniquet usage in two-staged hypospadias repair [4] .…”
Section: Discussionmentioning
confidence: 99%